2008
DOI: 10.1021/cc800081b
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Parallel Synthesis of Fused Heterocycles in a Novel Parallel Multimode Reactor

Abstract: New rotor types using disposable glass vials for small-scale parallel synthesis in multimode microwave reactors are introduced. One rotor comprises 16 groups of four vials, whereas the second uses four silicon carbide plates with a 6 x 4 matrix to process the vials. Both rotors achieve utmost temperature homogeneity upon microwave irradiation and can be used for microwave-mediated reactions at temperatures of up to 200 degrees C and pressures of 20 bar. The generation of three different heterocycle libraries f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 52 publications
0
24
0
4
Order By: Relevance
“…Microwave ovens provide a clean, economic, and attractive means of heating that is superior to conventional oil baths. Numerous reports highlighting the microwave‐assisted Gewald reaction have been published . Microwave irradiation in combination with heterogeneous catalysts has also been used for the efficient synthesis of 2‐aminothiophenes .…”
Section: Gewald Reaction Modificationsmentioning
confidence: 99%
“…Microwave ovens provide a clean, economic, and attractive means of heating that is superior to conventional oil baths. Numerous reports highlighting the microwave‐assisted Gewald reaction have been published . Microwave irradiation in combination with heterogeneous catalysts has also been used for the efficient synthesis of 2‐aminothiophenes .…”
Section: Gewald Reaction Modificationsmentioning
confidence: 99%
“…Banik and co-workers demonstrated that a solvent-free mixture of 2,5-dimethoxytetrahydrofuran and an amine with iodine (5 mol%) in an automated microwave oven afforded in short reaction time (∼5 min) N-substituted pyrroles in good yields (75-98%) [5]. A microwave process is highly beneficial in a small-scale parallel synthesis of 2-aminothiophenes by the Gewald reaction [6]. The 24 members of the 2-aminobenzo[b]thiophene library have been synthesized (10 min, 120 • C, in ethanol solution) in 22-78% yields and excellent purities.…”
Section: 23 Five-membered Heterocycles With N and S Atoms: Synthesimentioning
confidence: 99%
“…This approach involved trifluoroacetic acid (TFA) as catalyst [11]. (NH 4 ) 6 Mo 7 O 24 ·4H 2 O has also been used as catalyst [12]. Hydrazinolysis of substituted imidazo[1,2-a]pyrimidines into 4(5)-substituted 2-amino-1H-imidazoles has been performed under microwave irradiation at 120 • C [Eq.…”
Section: Synthesis Of Imidazoles and Related Compoundsmentioning
confidence: 99%
“…Although not applied to reaction monitoring per se, IR thermography has been used to probe the homogeneity of heating in silicon carbide well plates under microwave irradiation [23,24]. Silicon carbide is highly microwave absorbing, chemically inert, and has a very high thermal conductivity and melting point [25].…”
Section: Use Of Thermal Imaging Equipmentmentioning
confidence: 99%